2019
DOI: 10.1186/s12891-019-2564-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kinesio tape on lower limb muscle strength, hop test, and vertical jump performances: a meta-analysis

Abstract: Background: To date, published systematic reviews concerning the effects of Kinesio Taping (KT) on muscle strength have not analysed facilitatory and inhibitory applications separately. As a result, their results could be substantially affected by clinical heterogeneity. This meta-analysis was conducted to determine the effectiveness of using a facilitatory application of KT for lower limb muscle strength and functional performance (distance in a single-leg hop and vertical jump height) in individuals without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 69 publications
0
30
2
2
Order By: Relevance
“…They reported that using the ACL-KT technique with a 75% tension reduces knee abduction angle during a DVJ. Furthermore, KT provides tactile stimulation [ 23 , 44 ], although KT tactile inputs may not be strong enough to modulate muscle strength [ 13 ], and consequently, unable to moderate joint angles in healthy athletes during the double-leg landings of TLDVJ and DLFJ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that using the ACL-KT technique with a 75% tension reduces knee abduction angle during a DVJ. Furthermore, KT provides tactile stimulation [ 23 , 44 ], although KT tactile inputs may not be strong enough to modulate muscle strength [ 13 ], and consequently, unable to moderate joint angles in healthy athletes during the double-leg landings of TLDVJ and DLFJ.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is not possible to compare the present results with previous findings. However, various studies indicate that KT increases motor unit recruitment in healthy individuals, which might justify biomechanical changes affected by the KT technique [ 2 , 31 , 44 ]. Furthermore, the results revealed that KT has no effect on lateral trunk lean angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The taping methods of the KT-T on rectus femoris (RF), vastus medialis oblique (VMO), and vastus lateralis (VL) were as follows ( Lins et al, 2013 ; Poon et al, 2015 ; Fernandes de Jesus et al, 2016 ): (1) from a point 10 cm below the anterior superior iliac spine and split in the form of “Y” above the patella, finishing at tibial tuberosity (RF); (2) from the middle third of the medial thigh to the medial edge of the patella (VM); and (3) start from the greater trochanter of femur, finishing at the lateral edge of the patella (VMO). KT-T consistency with 50% tension was maintained in the muscles with the following equation, the leg length of the taping area was measured to calculate the actual length of the taping ( Yam M. L. et al, 2019 ; Yam T. T. T. et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of its special features, the compressive and shear force applied by the tape on the skin activates cutaneous mechanoreceptors related to joint position, movement, and force ( Kase et al, 2003 ), conveying more information from the knee joint to the central nervous system for integration and, therefore, resulting in enhanced proprioception ( Riemann and Lephart, 2002 ; Liu et al, 2019 ). Previous studies verified that the recoiling force direction of the tape is the same as that of a muscle contraction, is potentially transmitted to the fascia and facilitates a target muscle’s production of high force ( Kuo and Huang, 2013 ; Yam M. L. et al, 2019 ; Ye et al, 2019 ).…”
Section: Introductionmentioning
confidence: 91%